2018
DOI: 10.1007/s12325-018-0774-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Duration, Healthcare Resource Utilization, and Costs Among Chemotherapy-Naïve Patients with Metastatic Castration-Resistant Prostate Cancer Treated with Enzalutamide or Abiraterone Acetate: A Retrospective Claims Analysis

Abstract: IntroductionEnzalutamide and abiraterone acetate (plus prednisone) are new hormonal treatments for metastatic castration-resistant prostate cancer (mCRPC). This study compared treatment duration, healthcare resource utilization (HRU), and treatment costs for chemotherapy-naïve mCRPC patients treated with enzalutamide or abiraterone acetate in the USA.MethodsChemotherapy-naïve mCRPC patients initiating treatment with enzalutamide or abiraterone acetate were identified from administrative claims. Continuous enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
38
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 23 publications
9
38
1
Order By: Relevance
“…Our results were based on real-world data including patients who may not be eligible for clinical trials, which may have led to more frequent HCRU and higher costs compared with a model based on a healthier patient population. Findings of lower all-cause emergency room and PC-related inpatient costs in enzalutamide-treated patients have also been previously reported, although these patients incurred higher all-cause and PC-related pharmacy costs [ 18 ], whereas in our study, enzalutamide-treated patients had lower costs in all categories.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our results were based on real-world data including patients who may not be eligible for clinical trials, which may have led to more frequent HCRU and higher costs compared with a model based on a healthier patient population. Findings of lower all-cause emergency room and PC-related inpatient costs in enzalutamide-treated patients have also been previously reported, although these patients incurred higher all-cause and PC-related pharmacy costs [ 18 ], whereas in our study, enzalutamide-treated patients had lower costs in all categories.…”
Section: Discussionsupporting
confidence: 81%
“…There were fewer all-cause outpatient and pharmacy visits for enzalutamide-treated patients compared with abiraterone-treated patients. Schultz et al also found that treatment with enzalutamide, despite a higher occurrence of comorbid conditions, was associated with fewer inpatient and emergency department visits than abiraterone, likely attributed to corticosteroid use among abiraterone-treated patients [18]. In our PSM-matched cohorts, more abiraterone-treated patients used corticosteroids during the pre-index period than did enzalutamide-treated patients (45.69% vs 26.90%, respectively).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Treatment duration is a composite measure that does not distinguish between efficacy, tolerability and other causes of therapy discontinuation. However, it is a commonly reported metric in clinical trials and often a key outcome in observational studies of oncology treatments [3033]. Kaplan–Meier estimates of median time to discontinuation differed significantly by regimen in the first line of therapy: sorafenib had the shortest estimate (2.8 months) and vandetanib had the longest estimate (16.2 months).…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on COI analyses in the field of mCRPC, a recently published worldwide review [14] reported a broad range of cancer-specific healthcare costs, depending on the characteristics of included patients. However, only few studies have stratified costs by treatment, with most focusing exclusively on selected treatments-for example, hormonal therapy [15][16][17]-only considering pharmacy costs [15,18,19], and/or estimating costs for a hypothetical patient population (literaturebased cost analysis) [16,20]. Since mCRPC healthcare costs have not previously been reported for Germany [14,21] and the evidence for real-world outcomes of mCRPC stratified by contemporary treatment are limited, this study's purpose is to analyze the healthcare resource utilization (HRU) for patients with mCRPC and the costs of treatment with cabazitaxel, docetaxel, abiraterone, and enzalutamide in comparison with BSC.…”
Section: Introductionmentioning
confidence: 99%